Intranasal oxytocin blunts amygdala response to negative affective stimuli in males and females with alcohol use disorder: a randomized controlled cross-over trial - Vetter, Sina; Schnabel, Sophia; Reichl, Matthias; Sirignano, Lea; Grinevich, Valéry; Koopmann, Anne; Spanagel, Rainer; Kiefer, Falk; Sommer, Wolfgang H.; Bach, Patrick (Psychopharmacology, 2025)
Negative affect plays a prominent role in the maintenance of alcohol use disorder (AUD) and has been identified as a risk factor for relapse to alcohol. To date, however, treatment options that target negative affective states and consecutive relapse risk in AUD are insufficient. Oxytocin (OXY) might be a promising approach for addressing negative affective states and resulting motivation to use alcohol.